Novel inflammatory markers in the blood of patients with knee synovitis. Issue 7 (July 2021) - Gao, Kun; Zhang, Yong; Sun, Shufen; Lin, Baocheng; Liu, Weidong; Lai, Wenqiang; Wu, Yihong; Lin, Zhanpeng; Jiang, Yinglu; Cao, Yafei; Yu, Weiji; Chen, Dayu
Objective: Synovitis is a joint disease that seriously affects patient quality of life, but there are currently no diagnostic markers. The albumin to fibrinogen ratio (AFR) and monocyte to lymphocyte ratio (MLR) are non-invasive and cost-effective markers for various systemic inflammatory diseases. However, these markers have not yet been investigated for synovitis. This cross-sectional study evaluated the predictive ability of AFR and MLR in patients with non-specific knee synovitis. Methods: One hundred fifty-five patients with knee synovitis and 108 healthy control patients were enrolled. Patient characteristics, blood parameters, AFRs, and MLRs were assessed, and the diagnostic value of these factors was determined. Results: Among 125 patients included, patients with synovitis had a lower AFR and higher MLR than control subjects. The diagnostic values of AFR and MLR were 0.86 and 0.84, respectively, and higher compared with other parameters by receiver operating characteristic curve assessments. Additionally, MLR was negatively correlated with AFR. Late-stage patients showed significantly lower AFRs and significantly higher MLRs than early-stage patients. Binary logistic regression analyses indicated that AFR was an independent predictor for synovitis severity. Conclusions: The AFR and MLR had high diagnostic value for knee synovitis. The AFR was an independent predictor for synovitis severity.